Human mesenchymal stromal cells from adult and neonatal sources: comparative analysis of their morphology, immunophenotype, differentiation patterns and neural protein expression - Montesinos, J.J.; Flores-Figueroa, E.; Castillo-Medina, S.; Flores-Guzmán, P.; Hernández-Estévez, E.; Fajardo-Orduña, G.; Orozco, S.; Mayani, H. (Cytotherapy (Oxford, England), 2009)
Bone marrow (BM) has been recognized as the main source of mesenchymal stromal cells (MSC); however, MSC have also been detected in umbilical cord blood (UCB) and placenta (PL). In the present study, we obtained MSC from these three sources and characterized them in a comparative manner. MSC were obtained from BM, UCB and PL samples and analyzed to determine their morphology, cell-surface antigen (Ag) expression and differentiation potential. Particular emphasis was placed on the expression of neural markers. MSC were detected in 9/9, 11/104 and 5/5 samples from BM, UCB and PL, respectively. MSC populations comprised several morphologically distinct cell types, including neural-like cells. MSC were positive for ‘mesenchymal’ Ag (CD105, CD73 and CD90), although CD90 expression was very heterogeneous. Interestingly, CD13 expression was high in all three sources. In all cases, MSC showed osteogenic and chondrogenic differentiation; however, UCB MSC showed no adipogenic potential. Furthermore, MSC from UCB produced a different type of cartilage compared with MSC from BM and PL. It is noteworthy that in all three sources we detected the expression of neural proteins without any neural differentiation stimuli. A significant increase in the proportion of neural marker-positive MSC was observed in the presence of neural inducers. Our results indicate that PL may prove to be a more appropriate source for obtaining MSC than UCB, and suggest the possibility that a subpopulation of MSC may possess neural potential, which is favored by neural inducers.